The impact of wine label’s sensory descriptions in the consumers’ purchasing decision and consumer experience - Pelicano, Ana Carolina Lavos (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence